Development of Biogas Energy and its Impact on Users in Rural Nepal (Socio-Economic Development Panorama, 2008)
Energy is the key to development. The per capita energy consumption reflects the development situation of a country. In Nepal, feulwood is the primarily used in cooking in the rural area which has adversely affected the health condition of rural women. The potentiality of the development of biogas energy is very high in rural Nepal and it is mainly used for cooking. The smokeless energy in the household consumption has significantly reduced the workload of women and it has brought significant changes in their health condition. Though there is a huge potentiality of biogas energy development, it has to go many steps for its development. This paper highlights the present scenario and its historical development of biogas in Nepal. Moreover, it has deeply analyzed its effects on the rural biogas users mainly on women.   Socio-Economic Development Panorama, Vol. 1. No. 2(2007) pp. 47-62